Evolution and diversification of reproductive phased small interfering RNAs in Oryza species. Issue 5 (10th December 2020) - Tian, Peng; Zhang, Xuemei; Xia, Rui; Liu, Yang; Wang, Meijiao; Li, Bo; Liu, Tieyan; Shi, Jinfeng; Wing, Rod A.; Meyers, Blake C.; Chen, Mingsheng
Summary: In grasses, two types of phased, small interfering RNAs (phasiRNAs) are expressed largely in young, developing anthers. They are 21 or 24 nucleotides (nt) in length and are triggered by miR2118 or miR2275, respectively. However, most of their functions and activities are not fully understood. We performed comparative genomic analysis of their source loci ( PHAS ) in five Oryza genomes and combined this with analysis of high‐throughput sRNA and degradome datasets. In total, we identified 8216 21‐ PHAS and 626 24‐ PHAS loci. Local tandem and segmental duplications mainly contributed to the expansion and supercluster distribution of the 21‐ PHAS loci. Despite their relatively conserved genomic positions, PHAS sequences diverged rapidly, except for the miR2118/2275 target sites, which were under strong selection for conservation. We found that 21‐nt phasiRNAs with a 5′‐terminal uridine (U) demonstrated cis ‐cleavage at PHAS precursors, and these cis ‐acting sites were also variable among close species. miR2118 could trigger phasiRNA production from its own antisense transcript and the derived phasiRNAs might reversibly regulate miR2118 precursors. We hypothesised that successful initiation of phasiRNA biogenesis is conservatively maintained, while phasiRNA products diverged quickly and are not individually conserved. In particular, phasiRNA production is under the control of multiple reciprocal regulation mechanisms.